Synthesis and Hypolipidemic Activity of Modified Side Chain α-Asarone Homologues - Cruz, Adriana; Garduño, Letícia; Salazar, María; Martínez, Elizdath; Jiménez-Vázquez, Hugo A.; Díaz, Francisco; Chamorro, Germán; Tamariz, Joaquín (Arzneimittelforschung, 2001)
A series of homologues of α-asarone (1), containing variable size and functionality on the side chain attached to the aromatic ring, has been subjected to a study of structure-activity relationship. For most of the prepared derivatives, either with a carbonyl (8a-8e), a hydroxy group (9a-9e), or with a conjugated double bond (10a-10d), significant effects on serum lipoprotein cholesterol, LDL-cho-lesterol, HDL-cholesterol and triglycerides were displayed. The results showed an enhancement of the hypocholesterolemic activity as the length of the chain is decreased. Theoretical conformational and electrostatic potential analyses of 1 and olefins 10 suggest unfavorable steric interactions in the bulky superior side-chain homologues as the deactivating biological effect.
Keywords: α-Asarone, conformational analysis, hypocholesterol-emic effects, side-chain homologues